Carbon Interstitial Diffusion in gamma-Fe - Belova, Irina V.; Murch, Graeme E. (Diffusion Fundamentals, 2005)
n this paper, we employ a four-frequency model for carbon diffusion in austenite where interstitials can diffuse either as isolated species or pairs. We make use of the Okamura and Allnatt formalism that has recently been shown to be near exact. The general finding of a previous analysis of McKee is confirmed: the increase of both tracer and chemical carbon diffusion coefficients with carbon composition at 1000°C is largely a result of a much higher rate of rotation of an interstitial pair compared with isolated interstitials. However, we find that the carbon atoms move almost two times faster as a rotating pair than found originally by McKee.